Horizontal, Vertical, and Hybrid: An Empirical Look at the Forms of Accountability. Issue 9 (October 2020) - Reddick, Christopher G.; Demir, Tansu; Perlman, Bruce
The existing accountability research in public administration either provides conceptual analyses and definitions of forms of accountability or case studies on accountability. They focus on the structure of responsibility or responding behavior. This article is different in that it tests actors' perceptions of the three commonly cited forms of accountability identified in the literature—vertical, horizontal, and hybrid. We test accountability on a national survey sample of city managers across the United States. Our structural equation model indicates that there is both vertical and horizontal accountability present in city governments in the United States supporting a hybrid model. The results of this study add to the literature because most of the existing research on accountability does not test this important relationship nor examine actors' perceptions.